2023
DOI: 10.3390/universe9030113
|View full text |Cite
|
Sign up to set email alerts
|

Swift/UVOT: 18 Years of Long GRB Discoveries and Advances

Abstract: The Neil Gehrels Swift Observatory (Swift) has been in operation for 18 years. The Ultra-Violet/Optical Telescope (UVOT) onboard Swift was designed to capture the earliest optical/UV emission from gamma-ray bursts (GRBs), spanning the first few minutes to days after the prompt gamma-ray emission. In this article, we provide an overview of the long GRBs (whose prompt gamma-ray duration is >2 s) observed by the Swift/UVOT, and review the major discoveries that have been achieved by the Swift/UVOT over the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 267 publications
(383 reference statements)
0
3
0
Order By: Relevance
“…Such profiles generally exhibit structured features on timescales of up to 10 3 s. At early times, they may also be directly related to the prompt activity of the central engine of the GRB. The class of decays corresponds to about 50% of events (Oates 2023). These GRBs are characterized by a simple power-law decay of the optical flux with time.…”
Section: Temporal Profilesmentioning
confidence: 99%
“…Such profiles generally exhibit structured features on timescales of up to 10 3 s. At early times, they may also be directly related to the prompt activity of the central engine of the GRB. The class of decays corresponds to about 50% of events (Oates 2023). These GRBs are characterized by a simple power-law decay of the optical flux with time.…”
Section: Temporal Profilesmentioning
confidence: 99%
“…Thanks to this configuration, its rapid reaction capability and its long life time (already about 20 years), several new results have already been obtained with this mission, with reviews of the most important ones, inclusive of those obtained from statistical studies, already reported (see [110][111][112][113][114][115][116][117][118][119]). Among them, two important results, left open by Bep-poSAX and solved with Swift thanks to its rapid reaction capability, are the early afterglow properties of long GRBs and the afterglow of short GRBs (no afterglow of short GRBs was discovered with BeppoSAX).…”
Section: Swift and Its Role In The Progress Of The Grb Phenomenonmentioning
confidence: 99%
“…The burst was localised by the Neil Gehrels Swift Observatory's Burst Alert Telescope (Dichiara et al 2022) and followed up by the Very Large Telescope (VLT) X-shooter instrument (de Ugarte Postigo et al 2022;Malesani et al 2023), which determined that it occurred at a redshift of 0.151 and belongs to very near long GRBs (Oates 2023). It was also detected by a multitude of other instruments: AGILE/GRID (Piano et al 2022), AGILE/MCAL (Ursi et al 2022), BepiColombo/MGNS Send offprint requests to: J. Řípa, e-mail: ripa.jakub@gmail.com (Kozyrev et al 2022), Insight-HXMT & SATech-01/GECAM-C (HEBS; An et al 2023), INTEGRAL/SPI-ACS (Gotz et al 2022), Konus-WIND & SRG/ART-XC (Frederiks et al 2023), MAXI & NICER (Williams et al 2023), Solar Orbiter/STIX (Xiao et al 2022), STPSat-6/SIRI-2 (Mitchell et al 2022), and XMM-Newton (Tiengo et al 2023).…”
Section: Introductionmentioning
confidence: 99%